ANTESEDEN DAN KONSEKUENSI STRES KERJA PADA TENAGA KESEHATAN DI RSUP DR. SOERADJI TIRTONEGORO KLATEN - Khairimawati, Maudhyna; Setyawan, Didik; Noor, Finisha Mahaesti (Fakultas Ekonomi - Universitas Setia Budi, 2018)
His study aims to examine the causes of job stress that is influenced by work-family conflict and work load that impact on job satisfaction on health workers of RSUP dr. Soeradji Tirtonegoro Klaten. Data were collected through questionnaires distributed to 120 health workers at RSUP dr. Soeradji Tirtonegoro Klaten who is married. The sampling technique used is purposive sampling with the entire population of health workers in RSUP dr. Soeradji Tirtonegoro Klaten. The results showed that work-family conflict had positive effect on job stress, work load had positive effect to job stress, and job stress had no effect on job satisfaction. These results provide meaning that the cause of job stress on health workers at dr. Soeradji Tirtonegoro Klaten is a work-family conflict and a high workload.